2022
DOI: 10.1158/1538-7445.am2022-6169
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 6169: Identification of molecules mediating natural killer cell-pancreatic stellate cell interactions

Abstract: Pancreatic stellate cells (PSCs) are the main sources of cancer-associated fibroblasts in pancreatic ductal adenocarcinoma (PDAC), which account for at least 50% of PDAC’s total tumor volume and its dense desmoplastic stroma. In recent years, immune-stromal cell interactions have been the subject of research in a variety of diseases. Interestingly, natural killer (NK) cells are relatively understudied in PDAC and may be exploited to identify new treatment opportunities. We have explored how NK cell-PSC interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Interestingly, we have previously shown that fibroblasts express known NK cell ligands and hypothesized that CAFs interact with NK cells as a potential immunosuppressive mechanism in PDAC. 7 To further examine immune-stromal cell interactions in the PDAC tumor microenvironment (TME), we utilized Imaging Mass Cytometry (IMC), a novel multiplex imaging system that uses up to 40 metal-conjugated antibody markers to gain information of both tissue structure and single-cell data to conduct higher order proteomic single cell analysis. 8 This novel technology will provide a deeper understanding of the immune architecture in PDAC.…”
mentioning
confidence: 99%
“…Interestingly, we have previously shown that fibroblasts express known NK cell ligands and hypothesized that CAFs interact with NK cells as a potential immunosuppressive mechanism in PDAC. 7 To further examine immune-stromal cell interactions in the PDAC tumor microenvironment (TME), we utilized Imaging Mass Cytometry (IMC), a novel multiplex imaging system that uses up to 40 metal-conjugated antibody markers to gain information of both tissue structure and single-cell data to conduct higher order proteomic single cell analysis. 8 This novel technology will provide a deeper understanding of the immune architecture in PDAC.…”
mentioning
confidence: 99%